2020
DOI: 10.5770/cgj.23.421
|View full text |Cite
|
Sign up to set email alerts
|

Older Emergency Department Patients: Does Baseline Care Status Matter?

Abstract: Background Little is known about the prognostic differences between older emergency department (ED) patients who present with different formal support requirements in the community. We set out to describe and compare the patient profiles and patterns of health service use among three older ED cohorts: home care clients, nursing home residents and those receiving no formal support. Methods We conducted a secondary analysis of the Canadian cohort from the interRAI multinational ED study. Data… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 29 publications
2
5
0
Order By: Relevance
“…These ndings are consistent with previous literature which analyzed admission predictors of unscheduled ED visits. (22)(23)(24)(25) A plethora of research has been dedicated to examining variables predictive of admission in the older adult cohorts, yielding results consistent with our predictors. (26-29) Receiving home care was included less as an admission predictor in the literature, representing a plausible underreporting of this variables in uence on ED visit dispositions.…”
Section: Discussionsupporting
confidence: 69%
“…These ndings are consistent with previous literature which analyzed admission predictors of unscheduled ED visits. (22)(23)(24)(25) A plethora of research has been dedicated to examining variables predictive of admission in the older adult cohorts, yielding results consistent with our predictors. (26-29) Receiving home care was included less as an admission predictor in the literature, representing a plausible underreporting of this variables in uence on ED visit dispositions.…”
Section: Discussionsupporting
confidence: 69%
“…CTAS is an ordinal scale that ranges from one to five, with a score of one indicating the most emergent (resuscitation) and five the least urgent (non-urgent) [ 23 ]. Triage acuity was condensed into three categories, similar to prior ED studies in Canada, [ 24 ] as CTAS score one (0.8%) and five (4.9%) are relatively infrequent: scores of one and two were grouped as ‘emergent’, scores of three as ‘urgent’, and scores four and five grouped as ‘non-urgent’.…”
Section: Methodsmentioning
confidence: 99%
“…This time metric is commonly used in ED research of older persons and conveniently represents the top quartile of the length‐of‐stay data. 23 , 24 , 25 , 26 ED registration time was used as the point of reference when determining ED length of stay.…”
Section: Methodsmentioning
confidence: 99%
“…Data on mortality were not collected, although prior work has demonstrated that <1% of older Canadian patients will die in the ED, 16 and ≈5% will die within 1 month of presentation. 26 , 27 We used ED registration as the starting point for length of stay, which may have increased additional health system–based confounders associated with disposition time. Missing data were systematically missing, whereby particular sites provided no data on age, and only Quebec hospitals reported on interRAI ED Screener time or ED disposition.…”
Section: Limitationsmentioning
confidence: 99%